Industrial policy versus the middle-income trap: The case for directional thrust - Wade, Robert H. (Journal of Public Governance, 2016)
The number of non-western countries which have become developed in the past two centuries is less than 10, almost all small in population. This shocking stylized fact joins with other evidence to support the reality of a “middle-income trap” (MIT) or “non-convergence trap”, which tends to protect the existing hierarchy of the world economy – even though the post-Second World War development industry has claimed to promote catch-up growth. This paper summarizes evidence for the existence of a MIT, outlines several plausible mechanisms, explains why proactive trade and industrial policies are an almost necessary condition for a country to rise through the middle income range at more than a snail’s pace, and suggests some rules of thumb for how to do trade and industrial policies well – rather than less, in line with the Washington Consensus and bilateral and regional trade and investment agreements.